The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1161/01.cir.58.5.825
|View full text |Cite
|
Sign up to set email alerts
|

Chronic aortic regurgitation: the effect of aortic valve replacement on left ventricular volume, mass and function.

Abstract: CHRONIC AORTIC REGURGITATION/Gaasch et al. with the technical assistance ofL. M. Woodbury SUMMARY Serial echocardiographic left ventricular (LV) studies were performed in 19 patients before (preop) and after (postop) aortic valve replacement (AVR) for chronic aortic regurgitation (AR); the effect of AVR on LV volume, mass and function was determined from the echocardiographic data. In the 12 patients who were considered to have successful surgical results, the average LV end-diastolic dimension fell from a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(23 citation statements)
references
References 32 publications
0
21
1
1
Order By: Relevance
“…All prosthetic aortic valves are relatively stenotic2 13 compared with the normal aortic valve, and as such constitute an obligatory chronic afterload excess on the myocardium. This is particularly so in those patients with prior aortic stenosis in whom, because of the narrower aortic root, only smaller valve sizes could be inserted, and in whom a larger resting transprosthetic-valvular gradient 8 found in an echocardiographic study that improvement of the volumetric or dimensional abnormalities could be seen as early as 7 to 10 days after successful surgery, and that late systolic function may be better than preoperative function as myocardial regression proceeds. Observing that early (6 to 12 months) after aortic valve replacement for aortic insufficiency there were two groups of patients, those with substantial reductions in left ventricular chamber diameter and muscle cross-sectional area and those without, and that it was in the latter that the only two postoperative deaths occurred, they concluded that this constituted a "poor outcome" group.…”
Section: Methodsmentioning
confidence: 99%
“…All prosthetic aortic valves are relatively stenotic2 13 compared with the normal aortic valve, and as such constitute an obligatory chronic afterload excess on the myocardium. This is particularly so in those patients with prior aortic stenosis in whom, because of the narrower aortic root, only smaller valve sizes could be inserted, and in whom a larger resting transprosthetic-valvular gradient 8 found in an echocardiographic study that improvement of the volumetric or dimensional abnormalities could be seen as early as 7 to 10 days after successful surgery, and that late systolic function may be better than preoperative function as myocardial regression proceeds. Observing that early (6 to 12 months) after aortic valve replacement for aortic insufficiency there were two groups of patients, those with substantial reductions in left ventricular chamber diameter and muscle cross-sectional area and those without, and that it was in the latter that the only two postoperative deaths occurred, they concluded that this constituted a "poor outcome" group.…”
Section: Methodsmentioning
confidence: 99%
“…[235][236][237][238][239][240][241][242][243][244][245][246] With time, during which the ventricle develops progressive chamber enlargement and a more spherical geometry, depressed myocardial contractility predominates over excessive loading as the cause of progressive systolic dysfunction. This can progress to the extent that the full benefit of surgical correction of the regurgitant lesion, in terms of recovery of LV function and improved survival, can no longer be achieved.…”
Section: Pathophysiologymentioning
confidence: 99%
“…244,[247][248][249][250][251][252][253][254][255][256] A large number of studies have identified LV systolic function and end-systolic size as the most important determinants of survival and postoperative LV function in patients undergoing AVR for chronic AR. 235, Studies of predictors of surgical outcome are listed in Table 13.…”
Section: Pathophysiologymentioning
confidence: 99%
“…During the course of the current study, our strategy for patient management in aortic regurgitation was changed because of data implicating left ventricular function and severity of symptoms as important determinants of postoperative prognosis. '-8, 13,17,20,[30][31][32][33][34][35] Hence, many patients with left ventricular dysfunction in the current study underwent operation before the development of severe symptoms or impaired exercise capacity. Fifty-four of the 80 patients (68%) were able to complete stage I of our treadmill protocol, including 33 of 50 (67%) with subnormal ejection fractions.…”
Section: Pathophysiology and Natural History-aortic Valve Replacementmentioning
confidence: 99%